A modified invariant subspace method for solving partial differential equations with non-singular kernel fractional derivatives - Touchent, Kamal Ait; Hammouch, Zakia; Mekkaoui, Toufik (Applied mathematics and nonlinear sciences, 2020)
In this work, the well known invariant subspace method has been modified and extended to solve some partial differential equations involving Caputo-Fabrizio (CF) or Atangana-Baleanu (AB) fractional derivatives. The exact solutions are obtained by solving the reduced systems of constructed fractional differential equations. The results show that this method is very simple and effective for constructing explicit exact solutions for partial differential equations involving new fractional derivatives with nonlocal and non-singular kernels, such solutions are very useful to validate new numerical methods constructed for solving partial differential equations with CF and AB fractional derivatives.